Information ethics and behaviors of upper secondary students regarding the use of computers and the internet - Atichart Harncharnchai (2018)
© 2015 McFarland & Company, Inc. This study investigates the ethical attitude and computer and Internet use behavior of upper secondary students. It examines their intentions to use computers and Internet observing information ethics based on PAPA issues (privacy, accuracy, property, and accessibility). The theory of reasoned action (TRA) is used as a ground concept to propose a research model that explores attitudinal factors affecting behavioral intention, and behavioral intention, in turn influences actual behavior. To validate the model, surveyed data were collected from 1108 high school students in Lampang, Thailand. Confirmatory factor analysis (CFA) was used to analyze the trustworthiness of the measurement model and structural equation modeling (SEM) was employed to test the TRA in the students' information ethics context. The results showed that the model was a good fit with the data. Findings also revealed that attitude and subjective norms had positive relationships with students' intention. Among the observed PAPA variables, however, privacy was found to have very low impact on attitude while accuracy, property, and accessibility were found rather high. It is recommended that future studies should be made and that it is essential to educate students on the matter of information ethics.